Comprehensive Insight into Crohn's Disease: Diagnosis, Clinical Presentation, Complications and Treatment”: Review (Journal of the College of Basic Education, 2025)
Immune-related in nature, Crohn's disease (CD) is classified as an inflammatory bowel disease (IBD). Genetic, environmental, and microbiological variables combine to produce its etiology. Beyond its potential to impact any area of the gastrointestinal system, the pathophysiology includes elevated levels of interleukin (IL)-12, IL-17, and Th1 profile, as well as the impairment of tolerance responses and a jump in pro-inflammatory interleukins. Intestinal neoplasia, enteric fistulae, and fibrotic strictures are among the long-term consequences of unchecked inflammation. As a result, it is crucial to reduce inflammatory early and effectively. In addition to blood in the stool or rectum, signs and symptoms include exhaustion, anorexia, loss of weight, persistent diarrhea, and stomach discomfort. This situation may also be linked to extra-intestinal manifestations such erythema nodosum, anterior uveitis, osteoporosis, and arthritis, as well as disorders involving musculoskeletal, cutaneous, ophthalmic, hepatic, and hematological changes. Currently, the diagnostic inquiry might include clinical history, tests like ileocolonocopy, capsule endoscopy, and fecal calprotectin, as well as therapies to bring about and sustain remission. In this regard, biological substances, anti-inflammatory medications like corticosteroid and immunomodulators (for quick symptom relief during anti-tumor necrosis factor α therapy commencement), surgery, and non-pharmacological treatments all play a part in its treatment. Antibody production and infusion responses, infections, malignancies linked to immune-modulating medications and biologics, and damage to the liver and bone marrow are examples of adverse therapeutic reactions. In addition to providing more recent data for therapeutic therapy of CD, this review aims to provide a brief overview of its pathogenesis, surveillance, and related illnesses.